Increased urge for movement, physical and mental restlessness, fundamental symptoms of restricting anorexia nervosa?. Issue 3 (4th February 2020) - Casper, Regina C.; Voderholzer, Ulrich; Naab, Silke; Schlegl, Sandra
Abstract: Objective: Continued mobility in the presence of severe weight loss is a well known, yet insufficiently researched characteristic of anorexia nervosa (AN). This study was designed to assess the prevalence of the drive for activity, here operationalized as an increased urge for movement, physical restlessness, and mental restlessness. Method: Participants were 83 female consecutively admitted adolescent patients qualifying for a diagnosis of AN (ICD‐10), restricting subtype. Information collected included responses to a questionnaire inquiring retrospectively about physical and psychological reactions after significant weight loss (on average 12.5 kg) and to measures of psychiatric and eating disorder pathology and exercise behaviors at hospital admission. Results: Over 80% of AN patients reported experiencing, at least partly, either, an increased urge for movement, physical or mental restlessness after significant weight loss. Altogether 95.1% reported, at least partly, one or a combination of two or all three symptoms. The sensations coexisted with equally high levels of fatigue and loss of energy, typically observed in starvation. The increased urge for movement and physical restlessness were foremost associated with reported actual physical activity and with weight loss. By contrast, mental restlessness was strongly linked to the degree of eating disorder pathology and to the severity of psychiatric symptoms. Discussion: This is the first investigation of the presence of an increased urge for movement, physical restlessness, and mental restlessness after significant weight loss in patients with acute AN. The symptoms, given their high frequency and specificity, are likely pathogenic for AN and, if replicated, deserve to be considered for inclusion as diagnostic criteria for AN. Abstract : Continued mobility in the presence of severe weight loss is a well‐known, yet insufficiently researched characteristic of anorexia nervosa (AN). This study explored the question whether and to what extent AN patients might be aware of an increased urge to move and physical and mental‐restlessness at the time of their greatest weight loss. Over 80% of AN patients reported experiencing either, an increased urge for movement, physical or mental restlessness after significant weight loss. Altogether 95.1% reported one or a combination of two or all three symptoms. These findings suggest a unique physiological adaptation of energy regulating pathways in AN.